Kakanien als Gesellschaftskonstruktion - Wolf, Norbert Christian (Böhlau, 2011)
This monograph (professorial dissertation FU Berlin 2009) undertakes an interpretation of the entirety of Musil's monumental novel by placing the focus on its socio-analytical critique of contemporary society. It adapts Pierre Bourdieu's concept of the socio-analysis of literary texts, complemented by methodology from recent narratology, discourse and media theory, and is empirically grounded upon research from social and cultural history. Opening with a reconstruction of Musil's 'negative' anthropology and his concurrently analytical and constructivistic conception of the novel, as well as his essayistic, 'anti-filmic' poetics, the first part of the study profiles the socio-analytical implications of two major terms of his concept of the novel: firstly "Eigenschaftslosigkeit" (lack of inherent qualities or characteristics), and secondly "Möglichkeitssinn" (sense of possibility) or "Essayismus" (essayism). The main section of the study continues with a reading of The Man without Qualities as a social 'force field', beginning with an analysis of the narratively constituted chronotope and the social sphere of Kakania. It then turns to the central male and female figures of the novel (in the sections Heirs and Disinherited; Climbers and Stagnaters; Terrorists and Prophets, as well as Fallen Lovers; Sufferers of an 'obscure time-disease'; Adapters and Dissidents) and finally to the constellations and interactions of the characters in their aesthetic arrangements (in the sections Marriages in Crises; Orderless Circumstances, Gender Struggle; Attempts at Love beyond Marriage; and Rivalry over Principles and People; Ideologic Hostilities and Class Struggle). Special attention is paid to Musil's contemporary critique of a society in a contradictory process of modernisation, and to his concrete historical and ideological points of reference in the conflict strewn Austria and Germany of the preand inter-war years, as it is these to date neglected aspects that cause the uncompleted, and yet epoch-making, novel to appear so unique and incomparable. A final section considers the positioning of the novel and ist author in the contemporary literary field, as well as his indirect authorial self-analysis which occurs in a concealed manner throughout the fictional narration. With this socio-analysis of The Man without Qualities, Bourdieu's innovative cultural-sociological approach is for the first time applied in a consistent and detailed manner on a canonical German language novel. Moreover, an integral aspect of the study involves a theoretically aware integration of meticulous textual analysis and a broad cultural and literary historical contextualisation, which not only extends over Musil's essays and his voluminous literary remains (notes and drafts of sequels), but also over numerous discoursive involvements with contemporary Austrian and German politics and scholarship, and national and international literature. The Man without Qualities hence is presented as a modern classic of European literature, which relentlessly reveals the roots of the catastrophical history of the early twentieth century, and which transcends the sociological knowledge of its time.
Robert Musils Sozioanalyse des 20. Jahrhunderts
Keywords: Literatur; Kritik; Habitus; Ehe; Geschlechterbild; Gesellschaft; Homosexualität; 830 Literaturen germanischer Sprachen; Deutsche Literatur; 833 Deutsche Erzählprosa